100% renewable electricity in Australia. (15th August 2017) - Blakers, Andrew; Lu, Bin; Stocks, Matthew
Abstract: An hourly energy balance analysis is presented of the Australian National Electricity Market in a 100% renewable energy scenario, in which wind and photovoltaics (PV) provides about 90% of the annual electricity demand and existing hydroelectricity and biomass provides the balance. Heroic assumptions about future technology development are avoided by only including technology that is being deployed in large quantities (>10 Gigawatts per year), namely PV and wind. Additional energy storage and stronger interconnection between regions was found to be necessary for stability. Pumped hydro energy storage (PHES) constitutes 97% of worldwide electricity storage, and is adopted in this work. Many sites for closed loop PHES storage have been found in Australia. Distribution of PV and wind over 10–100 million hectares, utilising high voltage transmission, accesses different weather systems and reduces storage requirements (and overall cost). The additional cost of balancing renewable energy supply with demand on an hourly rather than annual basis is found to be modest: AU$25–30/MWh (US$19–23/MWh). Using 2016 prices prevailing in Australia, the levelised cost of renewable electricity (LCOE) with hourly balancing is estimated to be AU$93/MWh (US$70/MWh). LCOE is almost certain to decrease due to rapidly falling cost of wind and PV. Highlights: PV and wind allow Australia to reach 100% renewable electricity rapidly at low cost. Wide dispersion of wind and PV over 10–100 million hectares reduces cost. Off-river pumped hydro energy storage is the cheapest form of mass storage. There are effectively unlimited sites available in Australia. LCOE from a 100% renewable Australian electricity system is US$70/MWh (2017 prices).